Development of radio frequency identification walking stick (RFIWS) and performance studies of the system / Mohammad Farid Saaid. - Saaid, Mohammad Farid (2012)
In the past, walking sticks and dogs have been of great assistance to the blind. However, the conventional assistive methods are limited in providing accurate path directions with additional information such as the road names and nearby facilities. Hence, a Radio-Frequency Identification Walking Stick (RFIWS) system was developed as an enhancement to the conventional design. The system utilizes an Ultra—High Frequency (UHF) reader, tag and an antenna. The objectives of the research were to develop a Graphical User Interface (GUI) programming, database and output mechanism for RFIWS system, to studies the tags performances and to investigate the 13651 antenna position to place on walking stick in RFIWS system. In studies of tag detection performances for different tag types, the best lag is the Twister lag since it gives a longest detection distance and highest percentage of average returning signal. The studies of tag performances based on effect of antenna position In tag detection pattern justify that the tag detection patterns size can be improved with combining the position of antenna heights and angles. The different antenna position by combining the height and angle was produced a different size of tag detection patterns. In studies of detection performances based on the tag detection pattern justify that the lag detection strength can be study by measuring the percentage of total average returning signals. This experiment give the estimation area at the sidewalk for the blind safe during walking with the best percentage of total average returning signals is 78.65% by applying antenna height 30cm and angle 30“ in RFIWS system. As a conclusion, the best antenna position to place on walking stick in RFIWS system was at antenna height 300m with angle 30° which recorded 78.65% as the highest tag detection strength recorded.